National, regional, and worldwide estimates of stillbirth rates in 2015, with trends from 2000: a systematic analysis - Blencowe, Hannah; Cousens, Simon; Jassir, Fiorella Bianchi; Say, Lale; Chou, Doris; Mathers, Colin; Hogan, Dan; Shiekh, Suhail; Qureshi, Zeshan U; You, Danzhen; Lawn, Joy E; Zhu, Jun; et al. (The Lancet global health, 2016)
Previous estimates have highlighted a large global burden of stillbirths, with an absence of reliable data from regions where most stillbirths occur. The Every Newborn Action Plan (ENAP) targets national stillbirth rates (SBRs) of 12 or fewer stillbirths per 1000 births by 2030. We estimate SBRs and numbers for 195 countries, including trends from 2000 to 2015. We collated SBR data meeting prespecified inclusion criteria from national routine or registration systems, nationally representative surveys, and other data sources identified through a systematic review, web-based searches, and consultation with stillbirth experts. We modelled SBR (≥28 weeks' gestation) for 195 countries with restricted maximum likelihood estimation with country-level random effects. Uncertainty ranges were obtained through a bootstrap approach. Data from 157 countries (2207 datapoints) met the inclusion criteria, a 90% increase from 2009 estimates. The estimated average global SBR in 2015 was 18·4 per 1000 births, down from 24·7 in 2000 (25·5% reduction). In 2015, an estimated 2·6 million (uncertainty range 2·4–3·0 million) babies were stillborn, giving a 19% decline in numbers since 2000 with the slowest progress in sub-Saharan Africa. 98% of all stillbirths occur in low-income and middle-income countries; 77% in south Asia and sub-Saharan Africa. Progress in reducing the large worldwide stillbirth burden remains slow and insufficient to meet national targets such as for ENAP. Stillbirths are increasingly being counted at a local level, but countries and the global community must further improve the quality and comparability of data, and ensure that this is more clearly linked to accountability processes including the Sustainable Development Goals. Save the Children's Saving Newborn Lives programme to The London School of Hygiene & Tropical Medicine.